PENGGUNAAN MODEL THINK PAIR SHARE DALAM MENINGKATKAN KETERAMPILAN BERBICARA MAHASISWA PADA MATA KULIAH KAIWA II: Penelitian Eksperimen terhadap Mahasiswa Semester II Tahun Akademik 2022/2023 Program Studi Pendidikan Bahasa Jepang Universitas Negeri Jakarta - Irawan, Vaniya Safitri; Setiawati, Nia; Noverisa, Eva Jeniar (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2024)
The aim of this study is to evaluate the effectiveness of the Think Pair Share model in enhancing students' speaking skills in the Kaiwa course and to assess their responses to this model. Given the interaction challenges in online learning due to the COVID-19 pandemic and the use of applications such as Google Classroom and Zoom, the Think Pair Share model is recommended to improve speaking skills in this course at Universitas Negeri Jakarta. This study employs a pre-experimental design with a one-group pretest-posttest setup, involving a purposive sampling based on final exam scores from the first semester. The instruments used are tests to measure speaking skills before and after the treatment, and a questionnaire to evaluate students' responses. Data analysis results show an increase in the average score from the pretest (48) to the posttest (73), representing a 25-point improvement. The Think Pair Share model proves effective in enhancing students' speaking skills, with students reporting increased confidence, better understanding of the material, and greater ease in interaction.